Stopień współwystępowania regionalnych wahań koniunktury na przykładzie regionów Stanów Zjednoczonych - Welc, Jacek (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The scope of contemporaneity of changes in year-over-year growth pace of non-farm employment in the individual states of the USA has been explored in the paper. Regression equations' coefficients of determination and correlation coefficients between individual regions, as well as between regions and whole United States have been applied. The analysis found that the phases of business cycle appears in different regions in different points of time. It triggers the possibility of making significant mistakes in business planning and in carrying regional socioeconomic policy in the case of evaluating the current regional economic climate on the basis of macroeconomic business indeces. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 128-134